Implementasi Kebijakan Program Penanggulangan Stunting di Dinas Kesehatan Lamongan - Nada, Qothrun; Rosdiana, Weni (Universitas Negeri Surabaya, 2023)
The Stunting Management Program at the Lamongan Health Office aims to prevent and reduce the prevalence of undernutrition and malnutrition in Lamongan District and achieve optimal nutritional status for toddlers. The purpose of this research is to describe and analyze a Policy Implementation in the Regent's Regulation number 7 of 2019 regarding the Implementation of the Stunting Management Program Policy at the Lamongan Health Office. This research is a descriptive study with a qualitative approach. Data collected using interview techniques, observation and documentation. This research focuses on the Implementation of the Stunting Management Program at the Lamongan Health Office, Lamongan District, Lamongan Regency. This study uses the theory of Van Metter Van Horn which has six indicators, namely Size and Policy Objectives on the prevalence of stunting in Lamongan Regency which has decreased to 16% with the ZERO STUNTING program created by the Regent of Lamongan assisted by the Lamongan Health Office, and there is a problem, namely that there are many stunting toddlers who have not been recorded from the executor. The implemented program has not been fully implemented properly. there are limited human resources both in quality and quantity due to employee mutations so that the program is not optimally implemented. Funding resources have not reached all targets, there are still many toddlers with stunting that have not been recorded from the implementing agency. time resources, in CFC activities there are many schedules that are backwards not in accordance with the agreement or schedule that has been determined between the parents of the toddler and the executor. The characteristics of implementing agents are appropriate for implementing the program. Attitudes and Tendencies Executors respond well to the existence of the Stunting Management Program at the Lamongan Health Office and there are no objections, and support successful implementation. Communication that exists between organizations / between implementers is good but communication with the community is very poor, because many people do not understand IT. The economic, social and political environment still hinders the program, namely the economic conditions of the people who are middle to lower class and people's understanding of the program is still low, while the political environment is quite supportive of the program. It can be concluded that program implementers can monitor, evaluate and re-socialize the Implementation of the Stunting Management Program Policy at the Lamongan Health Office and provide direct assistance together according to PERBUP No.7 of 2019. Keyword: Implementation, Programs, and Stunting